Real-time reliability allocation algorithm of high-throughput communication channel under strong interference. Issue 3 (29th July 2019) - Luo, Xian; Liao, Rongtao; Deng, Guoru; Dai, Dangdang; He, Xiaolan; Hou, Zhixiang
In order to improve the anti-interference capability of high-throughput communication and improve the communication quality in performing real-time reliability allocation of high-throughput communication channel in the strong interference environment, a real-time reliability allocation algorithm of high-throughput communication channel under strong interference based on fractionally spaced equalisation and excess mean square error convergence criteria is proposed. In this algorithm, a high-throughput communication channel model is established; optimal symbol interval sampling is carried out to communication signals based on the expansion loss of the channel; the matched filter detection method is adopted for interference suppression of high-throughput communication channel to realise signal spectrum suppression; the fractionally spaced equalisation method is adopted for equalisation scheduling of the channel, and based on the excess mean square error convergence criteria, real-time reliability allocation of high-throughput communication channel under strong interference is realised. Simulation results show that in high-throughput communication channel allocation under strong interference, the method proposed in this paper provides good reliability, which improves real-time channel allocation capability, and channel equalisation, and improves communication quality with relatively low communication output error bit.